2014
DOI: 10.1002/bmc.3217
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography–electron ionization–mass spectrometry quantitation of valproic acid and gabapentin, using dried plasma spots, for therapeutic drug monitoring in in‐home medical care

Abstract: A simple and sensitive gas chromatography-electron ionization-mass spectrometry (GC-EI-MS) method using dried plasma spot testing cards was developed for determination of valproic acid and gabapentin concentrations in human plasma from patients receiving in-home medical care. We have proposed that a simple, easy and dry sampling method is suitable for in-home medical patients for therapeutic drug monitoring. Therefore, in the present study, we used recently developed commercially available easy handling cards:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…DBS cards have been compared in studies on HIV virus load; in contrast, only a few studies on AEDs have been conducted . Ikeda et al compared Whatman FTA DMPK‐A® and Bond Elut DMS® using valproic acid and gabapentin. Both cards demonstrated acceptable precision and accuracy, with DPS ranges of 10‐200 μg/mL for valproic acid and 0.5‐10 μg/mL for gabapentin (calibration curve r 2 > 0.99).…”
Section: Sample Preparation Of Dbsmentioning
confidence: 99%
See 1 more Smart Citation
“…DBS cards have been compared in studies on HIV virus load; in contrast, only a few studies on AEDs have been conducted . Ikeda et al compared Whatman FTA DMPK‐A® and Bond Elut DMS® using valproic acid and gabapentin. Both cards demonstrated acceptable precision and accuracy, with DPS ranges of 10‐200 μg/mL for valproic acid and 0.5‐10 μg/mL for gabapentin (calibration curve r 2 > 0.99).…”
Section: Sample Preparation Of Dbsmentioning
confidence: 99%
“…However, this could only be applied in participants with an Hct level of 30%‐49% . One interesting study of gabapentin by Ikeda et al compared outcomes using Whatman® FTA DMPK‐A® and Bond Elut DMS® paper; both demonstrated acceptable precision and accuracy using the DPS method, which ranged from 0.5 to 10 μg/mL (calibration curve r 2 > 0.99). However, the sample was unstable at 30°C; therefore, storage conditions below this temperature would enable the clinical application of gabapentin.…”
Section: Aed Concentration Measurement Using Dbs or Dpsmentioning
confidence: 99%
“…Therapeutic concentrations of gabapentin in treatment-refractory patients with partial seizures range from 2 to 20 mg/l [55]. HPLC [58], LC/MS-coupled GC [172], and GC-electron ionization-MS [173] methods have been used to quantify serum gabapentin.…”
Section: Newer Antiepileptic Drugsmentioning
confidence: 99%
“…Quantification of drugs using the dried plasma spot sampling technique has been described for daptomycin [10], valproic acid and gabapentin [11,12], linezolid [13], paroxetine [14], acetaminophen [15], guanfacine [16], iothalamate [17], vigabatrin [18], triazoles [19], and antiepileptic drugs [20], as well as anti-HIV drugs [21].…”
Section: Introductionmentioning
confidence: 99%